Hush Harbor : a novel - Vance, Anise (Hanover Square Press, 2023)
"After the murder of an unarmed Black teenager by the hands of the police, protests spread like wildfire in Bliss City, New Jersey. A full-scale resistance group takes control of an abandoned housing project and decide to call it Hush Harbor, in homage to the secret spaces their enslaved ancestors would gather to pray. Jeremiah Prince, alongside his sister Nova, are leaders of the revolution, but have ideological differences regarding how the movement should proceed. When a new mayor with ties to white supremacists threatens the group's pseudo-sanctuary and locks the city down, the collective must come to a decision for their very survival."--